PERANCANGAN USER INTERFACE (UI)/USER EXPERIENCE(UX) E-COMMERCE MENGGUNAKAN METODE LEAN UX DAN USER EXPERINXE QUESTIONNAIRE (UEQ) PADA IJOE BIRU CLOTHING UNTUK MENINGKATKAN EXPERIENCE PEMESANAN CUSTOM PRODUK DAN PEMBELIAN PRODUK - Mochamad Asyari Putra Pratama; Anjik Sukmaaji; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
E-commerce offers the convenience of buying and selling online, which can save time and money. Limited functionality in social media transactions makes it difficult to complete and obtain information about custom orders and product purchases. That is proven by customer interviews  with the results of 6 UEQ scales with “bad” criteria. The author intends to analyze and design e-commerce user interface (UI) / user experience (UX)  using  lean ux method and user experience questionnaire (UEQ) for the purpose of creating a user interface design  is well received by users. There are several phases of Lean UX including declaration assumption, create MVP, run an experiment, and feedback and research. The experiment consisted of  32 customer respondents  using the User Experience Questionnaire (UEQ) method. From the results of testing the prototype using UEQ, got 4 UEQ scales with above average criteria, "efficiency" with value 1.66, "precision" with value 1.84, "stimulation" with value 1.81, and a "novelty" with value 2.71. There is an increase in user experience when custom orders and purchasing products.